2013
DOI: 10.5539/jas.v5n3p179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salicylic Acid Pretreatment on Germination of Wheat under Drought Stress

Abstract: Seed priming increases enzyme of antioxidants such as glutathione and ascorbate in seed. These enzymes decrease the activities of lipid peroxidation in stage of germination. As a result, increases the percentage of germination. The aim of this survey is to study the effect of the pretreatment of salicylic acid under the condition of drought stress on features of germination.This research is performed in December 2011, in laboratory of seed control branch of Khuzestan. Wheat seeds of Chamran cultivars were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
2
13
0
2
Order By: Relevance
“…Minimum seed vigor was registered in a3b3 variant (priming with SA 0.75 mM + PEG 25%). These data are in accordance with the ones listed by Sharafizad et al, (2013). Control variants presented the highest values of measured characteristics while in medium to high concentration of PEG decreased significantly because the grains could not absorb this solution.…”
Section: Resultssupporting
confidence: 79%
“…Minimum seed vigor was registered in a3b3 variant (priming with SA 0.75 mM + PEG 25%). These data are in accordance with the ones listed by Sharafizad et al, (2013). Control variants presented the highest values of measured characteristics while in medium to high concentration of PEG decreased significantly because the grains could not absorb this solution.…”
Section: Resultssupporting
confidence: 79%
“…reported that increasing SA concentration enhances ABA synthesis which can inhibit seed germination. Sharafizad et al (2013) reported that pretreatment of wheat seeds with high concentrations (1.2 and 2.7 mM) of salicylic acid, compared to a low concentration (0.7 mM), reduced hypocotyl length. Accordingly, Zadehbagheri (2014) reported that pretreatment with high SA concentration (3 mM) damaged seed germination and seedling growth of corn while lower concentrations improved them in stress conditions.…”
Section: Plumule Lengthmentioning
confidence: 99%
“…Hundred healthy seeds for each treatment were selected manually by hand picking method. Various growth attributes such as Seed germination, Coefficient of velocity of germination (CVG), Germination rate (GI), Germination rate index (GRI), Coleoptile length, Root length, plantlet fresh and dry weight was calculated according to method given by Sharafizad et al(2013). In order to measured detail (CVG, GI, and GRI):CVG is characterized by speed and acceleration of germination and calculated from the following equation (Maguire, 1962).…”
Section: Methodsmentioning
confidence: 99%